Neural responses in a fast periodic visual stimulation paradigm reveal domain-general visual discrimination deficits in developmental prosopagnosia. (December 2020) - Fisher, Katie; Towler, John; Rossion, Bruno; Eimer, Martin
Abstract: We investigated selective impairments of visual identity discrimination in developmental prosopagnosia (DP), using a fast periodic identity oddball stimulation paradigm with electroencephalography (EEG). In Experiment 1, neural responses to unfamiliar face identity changes were strongly attenuated for individuals with DP as compared to Control participants, to the same extent for upright and inverted faces. This reduction of face identity discrimination responses, which was confirmed in Experiment 2, provides direct evidence for deficits in the visual processing of unfamiliar facial identity in DP. Importantly, Experiment 2 demonstrated that DPs showed attenuated neural responses to identity oddballs not only with face images, but also with non-face images (cars). This result strongly suggests that rapid identity-related visual processing impairments in DP are not restricted to faces, but also affect familiar classes of non-face stimuli. Visual discrimination deficits in DP do not appear to be face-specific. To account for these findings, we propose a new account of DP as a domain-general deficit in rapid visual discrimination.